Do Modifiable Cardiovascular Risk Factors Differ By Rural Classification in Women Who Enroll in a Weight Loss Intervention? - Dieu-My Thi Tran; Carol H Pullen; Lani M. Zimmerman; Patricia A Hageman (Rural Nurse Organization; Binghamton University, 2015)
Purpose: If clinicians and researchers are aware of specific cardiovascular risks associated with women's rural status, whether it be large or small/isolated rural areas, it may help in developing  more relevant rural resources. The purpose of this study was to examine whether there were differences in modifiable cardiovascular risk factors of overweight and obese rural women living in large or small/isolated rural areas.  Sample: This secondary analysis examined baseline cross-sectional data from the "Web-based  Weight Loss and Weight Maintenance Intervention for Older Rural Women" clinical trial.  Analysis included data from 299 rural Midwestern women, ages 40-69 years with a baseline body mass index of 28-45 kg/m2 into groups.  Methods: Demographic and biomarker baseline data were used. Chi-square and independent t-tests were used for data analyses. Findings: There are no significant differences found in overweight and obese women with cardiovascular risk factors when compared to rural classification, with one exception. Total cholesterol was associated with rural classification (p=0.047), where women living in large rural areas were more likely to have elevated total cholesterol levels (240 mg/dL) compared to women living in small/isolated areas (18.5% vs. 10.0%, respectively). Demographic characteristics such as age and education demonstrated no significant differences by rural classification; however, the majority of women in this study were of high socioeconomic status. Conclusions: Although this secondary analysis found that rural women have similar cardiovascular risk factors and demographic characteristics, this study highlights the need for clinicians to carefully consider the rural community characteristics for primary prevention.  Keywords: Cardiovascular risk factors, rural classification, middle-aged and older women. DOI:  http://dx.doi.org/ 10.14574/ojrnhc.v15i1.339